A Review of Atomic Layer Deposition for Nanoscale Devices - Riyanto, Edy; Rijanto, Estiko; Prawara, Budi (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2012)
Atomic layer deposition (ALD) is a thin film growth technique that utilizes alternating, self-saturation chemical reactions between gaseous precursors to achieve a deposited nanoscale layers. It has recently become a subject of great interest for ultrathin film deposition in many various applications such as microelectronics, photovoltaic, dynamic random access memory (DRAM), and microelectromechanic system (MEMS). By using ALD, the conformability and extreme uniformity of layers can be achieved in low temperature process. It facilitates to be deposited onto the surface in many variety substrates that have low melting temperature. Eventually it has advantages on the contribution to the wider nanodevices.